RANCANG BANGUN SISTEM MONITORING TINGGI, BERAT BADAN DAN INDEX MASSA TUBUH (IMT) MENGGUNAKAN NODEMCU ESP8266 BERBASIS ANDROID - M. Nanak Zakaria; Koesmarijanto Koesmarijanto; Mariyah El Qibthiyah (Politeknik Negeri Malang, 2022)
Generally, height and weight measurements are carried out separately as well as to determine the Body Mass Index must be calculated manually using specific formulas that not everyone understands, so it is difficult to know whether the body has reached a normal number or not. This study will provide suggested solutions to support the body to be healthy in measuring devices and android applications, for height measurement using ultrasonic sensors, weight using loadcell sensors and NodeMCU ESP8266 as data processors. The results of measuring height and weight appear on an LCD, the results of Body Mass Index (BMI) and the recommended solutions to meet standard body numbers in calculating BMI appear on the android application. Based on the results of the tests carried out, it is known that designing a measuring instrument with NodeMCU ESP8266 based on Android has been successfully carried out. The measuring instrument by implementing the Ultrasonic Sensor HC-SR04 as a height measurement can perform a success percentage of 96.95% and Loadcell Sensor as a weight measurement can perform the percentage of success is 98.97%, while in measuring Body Mass Index (BMI) can do a success percentage of 90.84%, the measuring instrument can also emit sound in the form of body condition in accordance with the measurement results obtained by the microcontroller with a success percentage of the sound output of 100% but has an average percentage of voice output delay variations of 2.1 seconds.